Molecular engineering with endohedral fullerenes: towards solid-state molecular qubits - Plant, SR (2010)
Information processors that harness quantum mechanics may be able to outperform their classical counterparts at certain tasks. Quantum information processing (QIP) can utilize the quantum mechanical phenomenon of entanglement to implement quantum algorithms. Endohedral fullerenes, where atoms, ions or clusters are trapped in a carbon cage, are a class of nanomaterials that show great promise as the basis for a solid-state QIP architecture. Some endohedral fullerenes are spin–active, and offer the potential to encode information in their spin-states. This thesis addresses the challenges of how to engineer the components of a scalable QIP architecture based on endohedral fullerenes. It focuses on the synthesis and characterization of molecules which may, in the future, permit the demonstration of entanglement; the optical read-out of quantum states; and the creation of quasi-one-dimensional molecular arrays. Due to its long spin decoherence time, N@C60 is the selected as the basic molecular unit for ‘coupled’ fullerene pairs, molecular systems for which it may be possible to demonstrate entanglement. To this end, isolated fullerene pairs, in the form of spin-bearing fullerene dimers, are created. This begins with the processing of N@C60 at the macroscale and leads towards the synthesis of 15N@C60-15N@C60 dimers at the microscale. High throughput processing is introduced as the most efficient technique to obtain high purity N@C60 on a reasonable timescale. A scheme to produce symmetric and asymmetric fullerene dimers is also demonstrated. EPR spectroscopy of the dimers in the solid-state confirms derivatization, whilst permitting the modelling of spin–spin interactions for 'coupled' fullerene pairs. This suggests that the optimum inter–spin separation for which to observe spin–spin coupling in powders is circa 3 nm. Motivated by the properties of the trivalent erbium ion for the optical detection of quantum states, optically–active erbium–doped fullerenes are also investigated. These erbium metallofullerenes are synthesized and isolated as individual isomers. They are characterized by low temperature photoluminescence spectroscopy, emitting in the infra- red at a wavelength of 1.5 μm. The luminescence is markedly different where a C2 cluster is trapped alongside the erbium ions in the fullerene cage. Er2C2@C82 (isomer I) exhibits emission linewidths that are comparable to those observed for Er3+ in crystals. Finally, the discovery of a novel praseodymium-doped fullerene is reported. The balance of evidence favours the structure being assigned as Pr2@C72. This novel endohedral fullerene forms quasi-one-dimensional arrays in carbon nanotubes, which is a useful proof-of-principle of how a scaled fullerene-based architecture may be achieved.